Blast Eye Injury After Mobile Phone Battery Explosion: A Case Report: Poster Presentation - Case Report - Ophthalmologist - Ariany, Dessira Rizka Tri; Eclipsia Yuniar, Merry Giovedi (Majalah Oftalmologi Indonesia, 2023)
Introduction : Injuries from mobile phone blasts have been on the rise in recent years. Mobile phone blasts cause serious ocular morbidity. We report a rare case of blast eye injury after mobile phone battery explosion. Case Illustration : A 16 years old woman presented with burning sensation on both the eyes, following a smartphone battery blast. Immediately, after disconnecting the phone from the charger, the battery exploded and the phone blew apart. Her presenting visual acuity was 1/300 and 1.0 in right eye and left eye. Examination revealed broad corneal haziness on right eye, charred lashes, circumciliary congestion, and multiple soot particles embedded over the cornea, conjunctiva, and the lid margins. The eyes were washed with copious ringer lactate and the debris was carefully removed. Topical preservative free lubricants, broad-spectrum antibacterial agent, corticosteroid, and cycloplegic agent were prescribed along with systemic nonsteroidal anti-inflammatory drug. The healing of epithelial defects started on the next day and was complete by the 14th day. Discussion : We describe an ocular blast injury due to mobile phone explosion. The mechanism of injury from battery blast could be a combination of mechanical (battery pieces), thermal, and chemical injuries. The vision can be saved if the ocular surface burns are treated promptly and properly. Conclusion : Mobile blast injury is emerging as a new mode of ocular trauma. Knowing proper management is very important to achieve the best result.